Archaic paradigms in standard Croatian accentual patterns on the example of verbs ending in -ovati / -evati - Delaš, Helena (Poznańskie Studia Slawistyczne, 2025)
The article discusses the accentual patterns of verbs ending in -ovati / -evati, in terms of the changes affecting these patterns in the standard Croatian language at the same time considering the history of Croatian. The paper investigates whether the accent in this category of verbs abides by the rules governing the relationship between the Proto-Slavic and standard Croatian accentual systems. The conclusion is that the old paradigmatic differences have largely been preserved (e.g. zíma, A zȋmu > zimòvati, but ljȅto, G ljȅta > ljȅtovati) and that we should resist the pressure of accentual changes such as vjeròvati, razlikòvati and so on since such accentual patterns significantly disrupt the continuity of the standard language.